Il topos del “giardino dei sentieri che si biforcano” e le sue declinazioni espressive postmoderniste - Graziani, Lorenzo (Status Quaestionis, 2020)
Among all Borges’ brilliant ideas, the most famous is perhaps the one around which the short story The Garden of Forking Paths is constructed; in this short story is described the structure of an imaginary novel in which there is no selection between alternative possibilities and every possible thing is actualized in a different universe line: in some cases, these lines can rejoin after splitting and then break up again. However, even if the “forking paths” seem to be inextricably linked to Borges’ short story, in this case we can say that the Argentinian writer, rather than inventing something new, has contributed in great measure to fix in the popular imagination what appears to be an ancient topos. The main goal of this essay is to analyze how this topos is adopted and developed in its own expressive potential by a consistent number of postmodernist writers.